Semisynthesis and biological evaluation of prenylated resveratrol derivatives as multi-targeted agents for Alzheimer’s disease - Thanchanok Puksasook (2018)
© 2017, The Japanese Society of Pharmacognosy and Springer Japan. Abstract: A series of prenylated resveratrol derivatives were designed, semisynthesized and biologically evaluated for inhibition of β-secretase (BACE1) and amyloid-β (Aβ) aggregation as well as free radical scavenging and neuroprotective and neuritogenic activities, as potential novel multifunctional agents against Alzheimer’s disease (AD). The results showed that compound 4b exhibited good anti-Aβ aggregation (IC50 = 4.78 µM) and antioxidant activity (IC50 = 41.22 µM) and moderate anti-BACE1 inhibitory activity (23.70% at 50 µM), and could be a lead compound. Moreover, this compound showed no neurotoxicity along with a greater ability to inhibit oxidative stress on P19-derived neuronal cells (50.59% cell viability at 1 nM). The neuritogenic activity presented more branching numbers (9.33) and longer neurites (109.74 µm) than the control, and was comparable to the quercetin positive control. Taken together, these results suggest compound 4b had the greatest multifunctional activities and might be a very promising lead compound for the further development of drugs for AD.